2009
DOI: 10.1523/jneurosci.4434-08.2009
|View full text |Cite
|
Sign up to set email alerts
|

Impaired Synaptic Vesicle Release and Immaturity of Neuromuscular Junctions in Spinal Muscular Atrophy Mice

Abstract: The motor neuron disease spinal muscular atrophy (SMA) causes profound muscle weakness that most often leads to early death. At autopsy, SMA is characterized by loss of motor neurons and muscle atrophy, but the initial cellular events that precipitate motor unit dysfunction and loss remain poorly characterized. Here, we examined the function and corresponding structure of neuromuscular junction (NMJ) synapses in a mouse model of severe SMA (hSMN2/delta7SMN/mSmnϪ/Ϫ). Surprisingly, most SMA NMJs remained innerva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

58
371
5

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 350 publications
(444 citation statements)
references
References 47 publications
58
371
5
Order By: Relevance
“…S3), indicating that the SMA mice are capable of expressing Z + agrin. However, the skipping of Z exons and the resulting Z + agrin protein deficiency in SMA MNs between P1 and P3 would impair postsynaptic AChR clustering, as observed at P5 in this SMA model (7)(8)(9).…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…S3), indicating that the SMA mice are capable of expressing Z + agrin. However, the skipping of Z exons and the resulting Z + agrin protein deficiency in SMA MNs between P1 and P3 would impair postsynaptic AChR clustering, as observed at P5 in this SMA model (7)(8)(9).…”
Section: Discussionmentioning
confidence: 74%
“…Major morphological and biochemical deficits have been found at neuromuscular junctions (NMJs) and sensory-motor synapses. NMJ defects are first detectable at postnatal day 5 (P5), including presynaptic defects of terminal arborization and intermediate neurofilament aggregation in MNs, poor postsynaptic organization of AChRs in muscle, as well as reduced synaptic vesicle density and release at the NMJ (7)(8)(9). Importantly, similar NMJ defects have been reported in type I (the most severe type) SMA human fetuses (10).…”
mentioning
confidence: 85%
“…In addition, reduced neurotransmitter release and decreased numbers of docked vesicles that precede axonal degeneration and/or motor neuron death have been reported at synapses of severe SMA mouse models (28,29). Notably, accumulation of synaptic vesicles (SVs) away from release sites was observed in SMA fetal samples (30).…”
mentioning
confidence: 99%
“…The proximate cause of these synaptic changes is unclear. Numerous hypotheses have been proposed, including functional abnormalities in axonal transport and/or calcium channel loss in the nerve terminals (25)(26)(27)(28)(29)(30), but none have explained the defects observed in SMA presynaptic regions.…”
mentioning
confidence: 99%
“…However, how suboptimal levels of SMN lead to SMA is largely unknown. Multiple studies in SMA mouse models revealed widespread synaptic defects in neuromuscular junctions (NMJs), including neurofilament accumulation, poor terminal arborization, immature endplates, reduced quantal content, disturbed calcium homeostasis, and decreased remodeling potential; these defects precede motor neuron death (Cifuentes-Diaz et al 2002;Le et al 2005;Jablonka et al 2007;Kariya et al 2008;Murray et al 2008Murray et al , 2012Kong et al 2009;Ling et al 2010;Ruiz et al 2010;Lee et al 2011), suggesting that the NMJ alterations are the initial consequence of SMN deficiency, Ó 2015 Hua et al This article is distributed exclusively by Cold Spring Harbor Laboratory Press for the first six months after the full-issue publication date (see http://genesdev.cshlp.org/site/misc/terms.xhtml). After six months, it is available under a Creative Commons License (Attribution-NonCommercial 4.0 International), as described at http:// creativecommons.org/licenses/by-nc/4.0/.…”
mentioning
confidence: 99%